Solvent selection and effect of extraction conditions on ultrasound-assisted extraction of phenolic compounds from galangal (Alpinia officinarum) - Ozdemir, Murat; Gungor, Veranur; Melikoglu, Mehmet; Aydiner, Coskun (Elsevier, 2024)
This study aimed to identify the appropriate extraction solvent and investigate the effect of temperature (20-70 degrees C), time (5-60 min), solvent/solid ratio (5-40), ethanol/water concentration (10-90%) and ultrasoundassisted extraction conditions (ultrasound power of 10-90% and ultrasound cycle of 1-9) on total phenolic content (TPC), 2,2-diphenyl-1-picrylhydrazyl (DPPH), 2,2 '-azino-bis (3-ethylbenzothiazoline-6-sulfonic acid) (ABTS) and total flavonoid content (TFC) of galangal extracts. All extraction conditions studied had significant effect (p <= 0.05) on TPC, DPPH, ABTS and TFC. Ethanol/water (50%) binary solution was found as the most appropriate extraction solvent. Temperature of 25 degrees C, extraction time of 20 min, ethanol/water concentration of 50%, solvent/solid ratio of 10, ultrasound power of 50% and ultrasound cycle of 5 were determined to be the most efficient extraction conditions which yielded TPC of 66.89 mg GAE/g, DPPH of 49.01% inhibition, ABTS of 147.43 mM TE/ml and TFC of 148.22 QE/g. Significantly positive or negative, very high, strong and moderate Pearson correlation coefficients were obtained among TPC, DPPH, ABTS and TFC values. Pearson correlation analysis revealed that very high correlations (r >= 0.90) existed between DPPH and ABTS (r = 0.907, p <= 0.01), and TPC and TFC (r = 0.939, p <= 0.01) for the ethanol/water concentration, and between DPPH and ABTS (r = 0.944, p <= 0.01) for the ultrasound power. The current study showed that phenolic compounds with high antioxidant activity could be extracted from galangal using the ultrasound-assisted extraction conditions determined.
Keywords: Ultrasound -assisted extraction; Phenolic compounds; Galangal; Antioxidant activity; Alpinia officinarum